Nationwide Analysis of Complex Midface Advancement in Pediatric Patients. Issue 3 (September 2022) - Kalmar, Christopher L.; O'Sick, Nicholas R.; Pontell, Matthew E.; Golinko, Michael S.
Background: The purpose of this study was to utilize a multicenter database to better understand preexisting comorbidities, postoperative complications, and hospital financial charges for pediatric patients undergoing complex midface advancement procedures. Methods: Retrospective cohort study was conducted of patients undergoing midface advancement, including Le Fort II (LF2), Le Fort III (LF3), and Monobloc procedures in the United States between 2010 and 2020 using the Pediatric Health Information System. Preexisting comorbidities, postoperative complications, and hospital admission charges among these cohorts were analyzed. Results: During the study interval, 91 patients underwent complex midface reconstruction. Median age was 12.7 years. Postoperative complication rate was 44.0%, and LF2 procedures had fewer surgical complications than LF3 ( P  < .001) and Monobloc ( P  < .001). Distraction osteogenesis was utilized in 29.7% of midface advancement procedures. LF2 procedures were less likely to require blood transfusions than LF3 ( P  < .001) and Monobloc ( P  < .001). Hospital admission charges tripled over the last 10 years ( P  = .004), and these charges varied significantly across regions of the country ( P  < .001). Patients undergoing LF2 had lower hospital admission charges than those undergoing LF3 ( P  < .001) and Monobloc ( P  < .001). Several patients (30.3%) chose a farther hospital than the one locally available. Conclusions: While midface advancement procedures are conceptually grouped together, LF2 has significantly lower surgical complications, blood transfusions, hospital lengths of stay, hospital admission charges, ICU lengths of stay, and ICU charges than LF3 or Monobloc procedures.